2017
DOI: 10.11648/j.cmr.20170602.15
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Long Acting Reversible Contraceptive Methods and Associated Factors Among Reproductive Age Women in <i>Adama Town, Oromia Regional State, Ethiopia</i>

Abstract: Abstract:The global population is expected to reach between 7.5 and 10.5 billion by the year 2050. Ethiopia is the second most populous country in Sub-Saharan Africa next to Nigeria. Total Fertility Rate of Ethiopia is 4.1 children per women; contraceptive prevalence rate is 29% for all child bearing age women. The prevalence of long acting reversible contraceptive methods (LARCs) in Ethiopia was very low (4.2%). The cause for low prevalence of LARCs is not known. Thisstudy assessed the acceptance and factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 7 publications
(23 reference statements)
3
18
3
Order By: Relevance
“…Regarding pattern of LARC methods use, birth control Implant was the method used by almost 9 out of ten mothers. This finding was in line with findings of most previous studies conducted in different parts of Ethiopia where Implant was used by at least three-fourths of mothers (27,(30)(31)(32)(33)(34)(35)(36)38,40,42,43,(45)(46)(47) and higher than findings of some studies (37,39,41). This could be because of convenience and privacy as implants are inserted under the skin into the upper arm area whereas…”
Section: Factors Associated With Larc Methods Usesupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding pattern of LARC methods use, birth control Implant was the method used by almost 9 out of ten mothers. This finding was in line with findings of most previous studies conducted in different parts of Ethiopia where Implant was used by at least three-fourths of mothers (27,(30)(31)(32)(33)(34)(35)(36)38,40,42,43,(45)(46)(47) and higher than findings of some studies (37,39,41). This could be because of convenience and privacy as implants are inserted under the skin into the upper arm area whereas…”
Section: Factors Associated With Larc Methods Usesupporting
confidence: 91%
“…Our finding was also higher than 22.9% (30) (27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) and found that our finding was higher than pooled prevalence.…”
Section: Factors Associated With Larc Methods Usecontrasting
confidence: 45%
See 1 more Smart Citation
“…Regarding pattern of LARC use, birth control Implant was the method used by almost 9 out of ten mothers. This finding was in line with findings of most previous studies conducted in different parts of Ethiopia where Implant was used by at least three-fourths of mothers (27,(30)(31)(32)(33)(34)(35)(36)38,40,42,43,(45)(46)(47) and higher than findings of some studies (37,39,41). This could be because of convenience and privacy as implants are inserted under the skin into the upper arm area whereas IUDs are inserted into the uterus.…”
Section: Operational and Term Definitionssupporting
confidence: 91%
“…Our finding was also higher than 22.9% (30) Bahir Dar town, Northern Ethiopia. We also calculated 23.84% pooled prevalence from eighteen facility or community based cross-sectional studies conducted in different corners of Ethiopia (27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)) and found that our finding was higher than pooled prevalence.…”
Section: Operational and Term Definitionsmentioning
confidence: 90%